Supervision as a technology for the improvement of primary health care - Coelho, Manuela de Mendonça Figueirêdo; Miranda, Karla Corrêa Lima; Bezerra, Sara Taciana Firmino; Guedes, Maria Vilaní Cavalcante; Cabral, Riksberg Leite (Rev Rene, 2012)
The objective was to describe the experience of planning and performing supervision along with the Family Health teams carried out by nurses as members of the management team of the Primary Health Care of the town of Maracanaú-CE, Brazil. 86 visits were conducted in health units, from June 2010 to June 2011. The moments of data collection regarding the process and organization of work were intensified, presented as a particular moment for immediate intervention, mediation and reflection on the problems found and the possibilities of overcoming them. The experience showed the effective contribution of nursing work in the management of services in the Family Health Strategy, contributing to the qualification of primary health care.